Humoral immune response in Oreochromis niloticus: modified direct agglutination test - Fernandes, Dayanne C. [UNESP]; Eto, Silas F. [UNESP]; Claudiano, Gustavo S. [UNESP]; Marcusso, Paulo F. [UNESP]; Vieira, Flávia C. F. [UNESP]; Shimada, Marina T. [UNESP]; Silva, Thiago F. A. [UNESP]; Souza, Elaine C.; Salvador, Rogério; Moraes, Julieta R. E. [UNESP]; Moraes, Flávio R. [UNESP] (Springer Nature, 2015)
Understanding the functional mechanisms of the humoral and cellular immune responses among teleost broadens the possibilities for intervention and improvement of vaccination methods. The aim of this study was to evaluate the dynamics of the humoral immune response, hematological biochemical changes, and electrophoretic profile of proteins in Oreochromis niloticus, when submitted to antigen stimulation using sheep erythrocytes in a single dose and with booster doses. Seventy O. niloticus were distributed in two groups (n = 35): one received a single dose and the other received two doses of antigen. Evaluations were made at the following predetermined times: zero (pre-immune, i.e., before inoculation with the first injection of sheep erythrocytes, negative control) and on 7th, 14th, 21st, and 28th days after the first immunization to evaluate the hemogram, biochemistry, and electrophoresis of proteins and direct hemagglutination. Twenty-eight days after antigen inoculation, it was observed that there had been an increase in the serum antibody titer and fractions gamma globulins after second antigen stimulation. The results suggest that teleost fish have the capacity to produce antibodies from a single stimulation, and a second antibody production wave after second stimulation.
Keywords: Electrophoresis; Hemogram; Immunology; Teleosts; Tilapia